Influence of Internal Structure on Breaking Process of Short-Lived Landslide Dams - Meng, Chu-Ke; Chen, Kun-Ting; Niu, Zhi-Pan; Di, Bao-Feng; Ye, Yu-Jian (Frontiers in Earth Science, 2021)
The diversity of the structure of the landslide dam will result in the difference in the seepage of the dam body. In this paper, based on two kinds of soil bodies of different particle gradations, six groups of structures of landslide dam are designed to generalize different seepage developments and breaking processes. The study shows that the saturation and evolution characteristics of the seepage of the landslide dam have a large influence on the breaking characteristics of the landslide dam. The more permeable the landslide dam is, the faster the saturation line will develop, i.e. the more serious the erosion of the soil body inside the dam body caused by water flow will be, which leads to the reduction in the shear strength of such type of landslide dam. Thus, in the experiment, it is found that the breaking form of the landslide dam with the full-coarse dam structure is dam slope instability, the breaking form of the landslide dam with the upper-fine-lower-coarse dam structure is first overtopping and then collapsing, and the breaking form of the landslide dams with the full-fine, upper-coarse-lower-fine, front-coarse-back-fine and front-fine-back-coarse dam structures is Overtopping. The empirical formula is fitted according to the time-saturation degree curve of the landslide dams of different breaking forms so as to predict the breaking forms of the landslide dams before the dam break. During the water storage process of the landslide dam, the saturation process of the seepage inside the dam body reduces the stability of the landslide dam, thus affecting the breaking characteristics of the landslide dam after the dam breaks. In the experiment, it is found that the growth rate of the saturation degree of the landslide dam is inversely proportional to the growth rate of the dam breach area, the peak flow of the dam breach generally increases as the coarse-grained soil content increases, and the peak flow always occurs at the end of the severe break stage.